Augustine and the mystery of the church - Lee, James K., 1982- (Project Muse, 2017)
Over the course of the past two centuries, Augustine's ecclesiology has been subject to interpretations that overdraw the distinction between the visible and invisible dimensions of the church, sometimes reducing the church to a purely spiritual, invisible reality, over against the visible church celebrating the sacraments; the empirical community is incidental, at best, and can be discarded. By contrast, this book argues that the church is a mystery that is visible and invisible. Far from discarding the visible, Augustine places greater emphasis on the empirical church as his thought develops. This study traces Augustine's ecclesiology from early writings to later works in order to demonstrate this thesis. His early thought is heavily influenced by Platonism and tends to focus on the ascent of the individual soul. After his study of Scripture in the 390s, Augustine gives priority to participation in the visible, sacramental community. In his mature thought, the church is one mystery (mysterium, sacramentum) revealed by Scripture, with visible and invisible aspects. This book explores Augustine's exegesis of biblical images of the church, such as body of Christ, bride of Christ, city of God, and sacrifice, in order to show how the visible community is intrinsic to the mystery of the church.